Long‐term entecavir or tenofovir disoproxil fumarate therapy in treatment‐naïve chronic hepatitis B patients in the real‐world setting. Issue 5 (28th November 2014) - Idilman, R.; Gunsar, F.; Koruk, M.; Keskin, O.; Meral, C. E.; Gulsen, M.; Elhan, A. H.; Akarca, U. S.; Yurdaydin, C.
Summary The aim of this study was to determine the long‐term efficacy of entecavir (ETV) and tenofovir disoproxil fumarate (TDF) on the natural course of disease in chronic hepatitis B patients (CHB) with/without cirrhosis in clinical practice. A total of 355 treatment‐naïve CHB patients were enrolled into the study. The primary outcome measure was viral suppression as defined by serum HBV DNA level <20 IU/mL. A secondary outcome measure was to determine the development of Hepatocellular carcinoma (HCC). Virological and biochemical responses were similar between the two treatment groups over time. The presence of cirrhosis and hepatitis B e antigen (HBeAg) positivity did not appear to impact viral suppression. The cumulative probability of HBeAg loss was 41% at 4 years of therapy. Hepatitis B surface antigen (HBsAg) loss occurred in four patients. Model for End‐Stage Liver Disease score was significantly improved from baseline to week 48 and 96 under antiviral therapy (P = 0.013, P = 0.01). HCC was diagnosed in 17 patients (4.8%). The cumulative probability of the development of HCC was 3.3% at 1 year and 7.3% at 4 years of therapy. The development of HCC was independently associated with older age (P = 0.031) and the presence of cirrhosis (P = 0.004). Serum creatinine levels and creatinine clearance remained stable over time. ETV and TDF effectively maintained virological and biochemical responses in long‐term follow‐up of CHB patients with/without cirrhosis. HCC may still develop, although at a lower rate, and is more likely to develop in patients with cirrhosis, especially in older patients.